Factors influencing impulse buying in live streaming: a systematic literature review - Yin, Xiaoxing; Hashim, Haslinda; Ab Aziz, Yuhanis (Universiti Putra Malaysia Press, 2024)
Live streaming has experienced a surge in popularity worldwide. It has become known as a prominent online shopping trend with significant potential for marketing (Y. Zhang et al., 2024). The global revenues generated through live streaming in 2022 exceeded US$423 billion and are expected to reach US$500 billion by 2023 (iiMedia research, 2022). A global report shows that 81 % of Internet users surveyed in China and 75 % in India have purchased on live streaming (Statista, 2024). Live streaming has emerged as an essential way for customers to make online purchases and for merchants to advertise their items, especially in China. In June 2023, there were 765 million live streaming viewers in China, with shopping content emerging as the most favoured genre among these viewers (Statista, 2023).